Properties of Command Constructions in TİD - A. Sumru Özsoy; Meltem Kelepir; Derya Nuhbalaoğlu; Emre Hakgüder (Dilbilim Araştırmaları Dergisi)
This paper focuses on the properties of command constructions in Turkish Sign Language (TİD). The nature and function of manual signs and nonmanual markers in command constructions in TİD are investigated to determine their prosodic, morphological, morphophonological, and syntactic properties. We show that TİD does not utilize any of the properties reported in the literature as an obligatory marker of commands in some spoken and sign languages. The only salient marker of commands we have identified is a nonmanual marker: (forward/sideward) head tilt.